Potensi Penerapan Teknologi Aerobic Granular Sludge (AGS) dalam Pengolahan Air Limbah Industri Tahu - Y. A. A. Hidayat; S Sumiyati; M. A. Budihardjo; N. I. Setianingsih (Jurnal Penelitian Pendidikan IPA, 2024)
The tofu industry produces high protein food but produces wastewater with high organic matter and ammonia which is the result of protein breakdown in soybean seeds during the extraction process. Small and Medium Enterprises (SMEs) sometimes neglect waste treatment due to limited resources. Indonesian regulations stipulate special quality standards for wastewater in the Regulation of the Minister of Environment of the Republic of Indonesia No. 5 of 2014 concerning Wastewater Quality Standards for Soybean Processing Businesses and/or Activities. Indicators of organic matter pollution are characterized by the parameters BOD 150 mg/l, COD 300 mg/l, TSS 200 mg/l, and pH 5-9. Meanwhile, tofu industrial wastewater without special treatment can exceed the quality standard with BOD levels of 5.000-10.000 mg/l and COD levels of 7.000-12,000 mg/l. To overcome this problem apart from using activated sludge, researchers are exploring the use of Aerobic Granular Sludge (AGS) technology. AGS involves aggregate microorganisms in granules to treat wastewater efficiently. This increases treatment efficiency, reduces space requirements, and handles high organic loads effectively. Although aerobic granular technology is promising, research is still ongoing to better understand its characteristics and optimize applications in various industries and environmental conditions. This study aims to explore the potential application of Aerobic Granular Sludge (AGS) technology in treating tofu industrial wastewater with high organic matter content and significant ammonia content so that it meets permitted quality standards.